2006
DOI: 10.1128/jcm.01638-05
|View full text |Cite
|
Sign up to set email alerts
|

Multitypic Hepatitis C Virus Infection Identified by Real-Time Nucleotide Sequencing of Minority Genotypes

Abstract: The prevalence of concurrent multitypic hepatitis C virus (HCV) infection is uncertain. A sensitive and specific approach to identifying minority HCV genotypes in blood is presented. Following serum extraction and reverse transcription PCR to amplify cDNA originating from the viral 5 noncoding region, the amplified product mixture was treated with genotype-specific restriction endonuclease to digest the dominant genotype. Residual amplicons were subjected to PCR cloning and then to real-time DNA sequencing usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
(28 reference statements)
3
17
0
1
Order By: Relevance
“…In addition, clonal sequence analysis identified dual infection of HCV genotypes in one case (HPA017). The frequency of dual infection and/or recombination in this study was higher than expected; however, it was within the range reported in other countries (3.8% in Australia [Bowden et al, 2005] [Buckton et al, 2006]; 20% in USA [Herring et al, 2004]). The efficiency of detecting multiple infections may depend on the number of HCV genotypes circulating in the study population.…”
Section: Considering That Genotype 6e Is Thought To Have Emerged Insupporting
confidence: 72%
“…In addition, clonal sequence analysis identified dual infection of HCV genotypes in one case (HPA017). The frequency of dual infection and/or recombination in this study was higher than expected; however, it was within the range reported in other countries (3.8% in Australia [Bowden et al, 2005] [Buckton et al, 2006]; 20% in USA [Herring et al, 2004]). The efficiency of detecting multiple infections may depend on the number of HCV genotypes circulating in the study population.…”
Section: Considering That Genotype 6e Is Thought To Have Emerged Insupporting
confidence: 72%
“…This is supported by a recent modeling study (26) suggesting that HCV reinfections frequently result in spontaneous clearance and by empirical data from a number of studies showing reinfection rates in PWID of 2 to 9% (27)(28)(29)(30). Other studies have suggested that reinfection is much more common in PWID (20 to 39% [31][32][33]), and differences may be due to needle exchange programs in the regions studied or sensitivities of the assays used.…”
Section: Gt3supporting
confidence: 60%
“…Suspected multiple-genotype infections were confirmed for previously genotyped sera by use of the methodology described in detail in a previous study (4). Briefly, after amplification of a fragment from the 5ЈNC region, products were checked by gel electrophoresis and treated with genotype-specific restriction endonucleases to digest the dominant genotype.…”
Section: Methodsmentioning
confidence: 99%